2020
DOI: 10.3390/ijerph17218099
|View full text |Cite
|
Sign up to set email alerts
|

Is Quarantine for COVID-19 Pandemic Associated with Psychological Burden in Primary Ciliary Dyskinesia?

Abstract: Background: Information on psychological impact of COVID-19 quarantine in primary ciliary dyskinesia (PCD), a chronic disorder with recurrent pulmonary exacerbations, is lacking. Psychological well-being was prospectively assessed during COVID-19 lockdown in Italy in a PCD population. Methods: we recruited 27 PCD patients and 27 healthy controls. To assess psychological well-being, psychological general well-being index and parenting stress index-short questionnaires were administered to participants ≥15 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Measures should be implemented to allow children and adolescents to attend school safely. Isolation can be unpleasant because of a reduction in social contacts however, it is extraordinarily effective in reducing the exposure of children and adolescents, whether healthy or affected by chronic lung disorders, to infections (182).…”
Section: Discussionmentioning
confidence: 99%
“…Measures should be implemented to allow children and adolescents to attend school safely. Isolation can be unpleasant because of a reduction in social contacts however, it is extraordinarily effective in reducing the exposure of children and adolescents, whether healthy or affected by chronic lung disorders, to infections (182).…”
Section: Discussionmentioning
confidence: 99%
“…However, they carefully shielded themselves by staying at home and avoiding public places. Another study in 27 children and adults with PCD also showed that all shielded carefully [ 31 ]. It is possible that people with PCD could be particularly burdened by facemasks due to chronic wet cough, constantly runny nose, hearing problems [ 14 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, for children with asthma and other chronic respiratory conditions, many studies also highlight the deterioration of mental health 29 and report of psychological fatigue 30 . However, for certain chronic diseases, such as Primary Ciliary Dyskinesia, both parental and patient stress levels appeared not to be affected 31 . Nevertheless, among the general paediatric population, it should not be overseen that social distancing and lockdown measures have been consistently associated with adverse psychological effects, 32,33 as well as with reduced physical activity 34–36 and increased use of TV and electronic devices 36,37 .…”
Section: Discussionmentioning
confidence: 99%